(untitled) (Research, Society and Development, 2022)
Introduction: Reactive lesions are commonly found in the clinical routine of the dental surgeon, have a multifactorial character and are due to irritative factors such as dental calculus, extensive or deficient restorations, poorly adapted prostheses, dental implants, orthodontic brackets and foreign bodies. Objective: The objective was to report a case of non-neoplastic proliferative lesion located in the gingiva. Case report: Patient J. P. A., 63 years old, male, feoderm, was referred to the Periodontics Service of the Clinical Research Laboratory (Labclin), due to the presence of a lesion in the gingiva, located between elements 21 and 23. presented systemic and extraoral alterations, verified through anamnesis and extraoral clinical examination. In the intra-oral clinical examination, there was an exophytic, sessile lesion, with a pink color similar to the mucosa, lobulated surface, located in the gingiva in the anterior region of the maxilla and extending to the palate region. The lesion measured about 22 millimeters. In the evaluation of the radiographic image, there were no signs of any bone alteration. At first, because it was an extensive lesion, an incisional biopsy was performed, with the diagnostic hypothesis of fibrous pyogenic granuloma. Obtaining the histopathological result of pyogenic granuloma. In the second surgical moment, with the aim of total removal of the lesion, an excisional biopsy was performed, in which the diagnosis of a nonspecific chronic inflammatory process suggestive of foreign body granuloma was obtained. Conclusion: Therefore, having knowledge about these injuries, knowing how to differentiate them, diagnosing them is extremely important to provide the foundation for adequate planning and intervention.